Hepatic Hdac3 promotes gluconeogenesis by repressing lipid synthesis and sequestration - Sun, Zheng; Miller, Russell A; Patel, Rajesh T; Chen, Jie; Dhir, Ravindra; Wang, Hong; Zhang, Dongyan; Graham, Mark J; Unterman, Terry G; Shulman, Gerald I; Sztalryd, Carole; Bennett, Michael J; et al. (Nature medicine, 2012)
It is believed that lipid accumulation in the liver, or fatty liver disease, contributes to insulin resistance in this organ and, thus, poorly controlled gluconeogenesis and hyperglycemia during type 2 diabetes. Mitch Lazar and colleagues now show that deletion of the chromatin modifier Hdac3 in mice results in increased fatty liver disease but improved hepatic insulin sensitivity because metabolic flux in the liver is increased toward lipid synthesis and storage and away from gluconeogenesis. Fatty liver disease is associated with obesity and type 2 diabetes, and hepatic lipid accumulation may contribute to insulin resistance. Histone deacetylase 3 (Hdac3) controls the circadian rhythm of hepatic lipogenesis. Here we show that, despite severe hepatosteatosis, mice with liver-specific depletion of Hdac3 have higher insulin sensitivity without any changes in insulin signaling or body weight compared to wild-type mice. Hdac3 depletion reroutes metabolic precursors towards lipid synthesis and storage within lipid droplets and away from hepatic glucose production. Perilipin 2, which coats lipid droplets, is markedly induced upon Hdac3 depletion and contributes to the development of both steatosis and improved tolerance to glucose. These findings suggest that the sequestration of hepatic lipids in perilipin 2–coated droplets ameliorates insulin resistance and establish Hdac3 as a pivotal epigenomic modifier that integrates signals from the circadian clock in the regulation of hepatic intermediary metabolism.